Human CD4+CD25+CD226- Tregs Demonstrate Increased Purity, Lineage Stability, and Suppressive Capacity Versus CD4+CD25+CD127lo/- Tregs for Adoptive Cell Therapy - Brown, Matthew E.; Peters, Leeana D.; Hanbali, Seif R.; Arnoletti, Juan M.; Sachs, Lindsey K.; Nguyen, Kayla Q.; Carpenter, Emma B.; Seay, Howard R.; Fuhrman, Christopher A.; Posgai, Amanda L.; Shapiro, Melanie R.; Brusko, Todd M. (Frontiers in Immunology, 2022)
Regulatory T cell (Treg) adoptive cell therapy (ACT) represents an emerging strategy for restoring immune tolerance in autoimmune diseases. Tregs are commonly purified using a CD4+CD25+CD127lo/- gating strategy, which yields a mixed population: 1) cells expressing the transcription factors, FOXP3 and Helios, that canonically define lineage stable thymic Tregs and 2) unstable FOXP3+Helios- Tregs. Our prior work identified the autoimmune disease risk-associated locus and costimulatory molecule, CD226, as being highly expressed not only on effector T cells but also, interferon- (IFN-) producing peripheral Tregs (pTreg). Thus, we sought to determine whether isolating Tregs with a CD4+CD25+CD226- strategy yields a population with increased purity and suppressive capacity relative to CD4+CD25+CD127-/lo cells. After 14d of culture, expanded CD4+CD25+CD226- cells displayed a decreased proportion of pTregs relative to CD4+CD25+CD127lo/- cells, as measured by FOXP3+Helios- expression and the epigenetic signature at the FOXP3 Treg-specific demethylated region (TSDR). Furthermore, CD226- Tregs exhibited decreased production of the effector cytokines, IFN-, TNF, and IL-17A, along with increased expression of the immunoregulatory cytokine, TGF-1. Lastly, CD226- Tregs demonstrated increased in vitro suppressive capacity as compared to their CD127lo/- counterparts. These data suggest that the exclusion of CD226-expressing cells during Treg sorting yields a population with increased purity, lineage stability, and suppressive capabilities, which may benefit Treg ACT for the treatment of autoimmune diseases.